Obesity and discrimination: The next 'big issue'?. (September 2014) - Flint, Stuart W; Snook, Jeremé
A concomitant increase has been observed between the prevalence of obesity and the stigmatization and discrimination of the condition. Despite reports of such negative experiences, there appears to be little deterrence for individuals to behave in a non-discriminatory fashion towards the overweight and obese. This article focuses on an emergent academic, legal and medical debate concerning obesity and human well-being and its possible impacts in the workplace and on disability discrimination laws. The disability laws in the United Kingdom require employers and employees not to discriminate or harass their colleagues, yet the model of discrimination seen in the United Kingdom emerges from a historical basis where sex and race were accommodated by theSex Discrimination Act (1975) and theRace Relations Act (1976) respectively, and laws prohibiting disability were introduced later by the Disability Discrimination Act (1995). These laws in conjunction required UK citizens in the workplace and beyond not to subject their fellow citizens, potential workmates and current employees to less favourable treatment and to provide reasonable adjustments in the workplace where discrimination was a possible outcome of behaviours or policy arrangements.